2021
DOI: 10.1111/boer.12297
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social networking on labor market participation

Abstract: We study the impact of social networks on the workers' labor market participation. We assume that individuals are heterogeneous with respect to the value of home production, which determines who participates in the labor market. Active individuals strategically form social links to obtain job information where the opportunity cost of networking is the value of home production. We find that social networking increases the labor market participation because it raises the probability to find a job. However, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Its effects arise from the information, influence, and solidarity made available to the actor (Adler & Kwon, 2002). Social capital also determines how and what kind of job (Lancee, 2012) with what probability of success (Horvath & Zhang, 2022) would job-seekers find. Thus, building social capital is considered one of the most effective job search strategies (Karaoglu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Its effects arise from the information, influence, and solidarity made available to the actor (Adler & Kwon, 2002). Social capital also determines how and what kind of job (Lancee, 2012) with what probability of success (Horvath & Zhang, 2022) would job-seekers find. Thus, building social capital is considered one of the most effective job search strategies (Karaoglu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Connections between people and organizations are exponentially increasing thanks to online social networks, which have enabled unimaginable interactive dynamics of relationships (de Mesa et al, 2020). Although individuals recognize the importance of building their connections as a source of social capital, they often do not engage in such behaviors (Horvath & Zhang, 2022). However, studies within this perspective suggest that the greater a job-seekers' social capital is, the better information they would have, and more likely, it would lead to finding a job (Mowbray & Hall, 2021;Porter & Woo, 2015;Weiler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Horváth and Zhang (2022) studied how the formation of social networks affects the labor market participation of workers. They found that social networks raise the probability to find a job.…”
Section: Introductionmentioning
confidence: 99%